2020
DOI: 10.1126/sciadv.abb4377
|View full text |Cite
|
Sign up to set email alerts
|

Early development of the Neanderthal ribcage reveals a different body shape at birth compared to modern humans

Abstract: Ontogenetic studies provide clues for understanding important paleobiological aspects of extinct species. When compared to that of modern humans, the adult Neanderthal thorax was shorter, deeper, and wider. This is related to the wide Neanderthal body and is consistent with their hypothetical large requirements for energy and oxygen. Whether these differences were already established at birth or appeared later during development is unknown. To delve into this question, we use virtual reconstruction tools and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 55 publications
(129 reference statements)
0
23
0
2
Order By: Relevance
“…Loss-of-function mutations in the gene have been found in patients with cleidocranial dysplasia, an autosomal dominant disorder clinically character-4 ized by short stature, incomplete and delayed closure of fontanelles, frontal bossing, hypoplasia of clavicles or bell shaped thorax [35]. As previously highlighted by [45,46], some of the anatomical structures affected by RUNX2 dysfunction are known to differ between our species and the Neanderthals: the closure of fontanelles may be delayed in Homo sapiens in light of the globularization phase that takes place after birth and only attributed to our species [30,[47][48][49], or the wider lower thorax in a characteristically bell shape present in the Neanderthals [2].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Loss-of-function mutations in the gene have been found in patients with cleidocranial dysplasia, an autosomal dominant disorder clinically character-4 ized by short stature, incomplete and delayed closure of fontanelles, frontal bossing, hypoplasia of clavicles or bell shaped thorax [35]. As previously highlighted by [45,46], some of the anatomical structures affected by RUNX2 dysfunction are known to differ between our species and the Neanderthals: the closure of fontanelles may be delayed in Homo sapiens in light of the globularization phase that takes place after birth and only attributed to our species [30,[47][48][49], or the wider lower thorax in a characteristically bell shape present in the Neanderthals [2].…”
Section: Discussionmentioning
confidence: 87%
“…Neanderthals are known to have an overall higher bone density, probably coupled with higher muscle mass relative to Homo sapiens [1]. Different developmental trajectories [2] lead to clear differences in structures like the lower thorax [3], the 1 lumbo-pelvic complex [3,4], and in general give rise to relatively large limb length and a shorter stature [5].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding scapular development (changes in shape with age), previous research suggested that postnatal ontogenetic development only accentuates the features already present prenatally or at an early postnatal stage 28 , 30 , 66 . However, it is interesting to note here that the scapular development of chimpanzees and humans is convergent, in that juvenile human and chimpanzee morphology is more divergent relative to that seen in older individuals.…”
Section: Discussionmentioning
confidence: 99%
“…From an evolutionary point of view, the study of developmental changes that occurred during prenatal and postnatal ontogeny could provide important information of phylogenetic interest 19 , 24 , 29 , 30 . Adult morphologies can vary between species because of (1) differences in the shape of the anatomical element at the moment of birth that is caused by differences in the prenatal ontogenetic trajectories; (2) differences in the shape of the anatomical element that arise after birth and are caused by differences in the postnatal ontogenetic trajectories; and (3) differences in the magnitude of the ontogenetic change after birth 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Este hecho repercute directamente en el tamaño de dientes e inserciones musculares alojadas en la mandíbula de estos individuos, siendo mucho más voluminosos en la zona medio facial que la especie Homo sapiens. Precisamente esta curiosa morfología facial es la que, según algunos estudios, habría permitido una gran adaptación al frío y una alta demanda energética (Azevedo et al, 2017;Wroe et al, 2018;García-Martínez et al, 2020). Según algunos estudios, se ha podido comprobar que los individuos neandertales poseerían una mayor agudeza visual con respecto a Homo sapiens (García-Tabernero et al, 2018), todo ello a partir del análisis de la superficie endocraneal del occipital de los primeros, que muestra diferencias significativas con estos últimos.…”
Section: Las Morfologías Dentarias En Homo Sapiensunclassified